Aeromonas salmonicida type III secretion system-effectors-mediated immune suppression in rainbow trout (Oncorhynchus mykiss). Issue 60 (January 2017) - Origgi, F.C.; Benedicenti, O.; Segner, H.; Sattler, U.; Wahli, T.; Frey, J.
Abstract: Aeromonas salmonicida subsp. salmonicida, the etiologic agent of furunculosis, is a major pathogen in aquaculture. Together with other pathogens, it is characterized by the presence of a type 3 secretion system (T3SS). The T3SS is the main virulence mechanism of A. salmonicida. It is used by the bacterium to secrete and translocate several toxins and effector proteins into the host cell. Some of these factors have a detrimental impact on the integrity of the cell cytoskeleton, likely contributing to impair phagocytosis. Furthermore, it has been suggested that effectors of the T3SS are able to modulate the host's immune response. Here we present the first partial characterization of the immune response in rainbow trout ( Oncorhynchus mykiss ) infected with distinct strains of A. salmonicida either carrying (i) a fully functional T3SS or (ii) a functionally impaired T3SS or (iii) devoid of T3SS ("cured" strain). Infection with an A. salmonicida strain either carrying a fully functional or a secretion-impaired T3SS was associated with a strong and persistent immune suppression. However, the infection appeared to be fatal only in the presence of a fully functional T3SS. In contrast, the absence of T3SS was neither associated with immune suppression nor fish death. These findings suggest that the T3SS and T3SS-delivered effector molecules and toxins of A. salmonicida do not only impair the host cells' cytoskeleton thus damaging cell physiology and phagocytosis, but also heavily affect the transcription of critical immune mediators including the shut-down of important warning signals to recognize infection and induce immune defense. Highlights: Type 3 secretion system of Aeromonas salmonicida is associated with immunosuppression in fish. The presence of a functional type 3 secretion system is associated with death in fish infected with Aeromonas salmonicida. Aeromonas salmonicida with a defective type 3 secretion system is not lethal but still causes immunosuppression. Infection with Aeromonas salmonicida " cured" (no T3SS and effector genes) is not lethal and causes no immunosuppression.